2019
DOI: 10.3390/pharmacy7020037
|View full text |Cite
|
Sign up to set email alerts
|

Competency and Its Many Meanings

Abstract: Competency and competency assessment are central to much of professional education, regulation, and practice. In the name of safe and effective professional practice, elaborate competency education and competency assessment systems have evolved, and consume significant time, energy, and financial resources. This paper will review the evolution of competing competency discourses in pharmacy and discuss implications of these approaches on professional practice, with particular emphasis on understanding the conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…They are observable components of knowledge, skills, attitudes and values expressed as actual behaviour which can be measured and assessed [ 2 ]. However, in health professions education, understandings of what pertain to competency have evolved over time, leading to a variety of interpretations with contested “meanings” [ 3 ]. Competence (the ability to carry out a job or task) is also considered multi-faceted, context-driven and dynamic, but generally prescribes the “integration of abilities across multiple domains and aspects of health care professional performance in a certain context” [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…They are observable components of knowledge, skills, attitudes and values expressed as actual behaviour which can be measured and assessed [ 2 ]. However, in health professions education, understandings of what pertain to competency have evolved over time, leading to a variety of interpretations with contested “meanings” [ 3 ]. Competence (the ability to carry out a job or task) is also considered multi-faceted, context-driven and dynamic, but generally prescribes the “integration of abilities across multiple domains and aspects of health care professional performance in a certain context” [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Competency is no stranger concept to the pharmacy profession and it may have many meanings [10]. In 2012, the International Pharmaceutical Federation (FIP) developed the Global Competency Framework (GbCF) for services provided by pharmacy workforce [11] based on education developmental frameworks for pharmacists to aid its members to navigate this complex concept.…”
Section: Introductionmentioning
confidence: 99%
“…But, all terms in the current study were handled them on an academic basis. Hager and Gonczi in 1996, Austin in 2019, Bates in 2020, Fukada in 2018, Wu and Martin, in 2019, Salman et al, in 2020 reported that competency describes that the people have a chain of required characteristics involving attitudes or values, knowledge, skills and capabilities such as critical thinking, leadership, and communication skills that allow them to do any task successfully. Or, it is the person's aptitudes to execute something successfully or efficiently.…”
mentioning
confidence: 99%
“…Competency refers to a cluster of cognitive, affective, and behavioral abilities that were explained in cognitivin, humanism, behaviorism, and social learning theories. (Hager and Gonczi, 1996, Austin, 2019, Bates, 2020, Fukada, 2018, Wu and Martin, 2019, Salman et al, 2020, Mulder et al, 2006, , Jung et al 2020, and Koster 2017 Competency is translated into the ability to confirm the link between the theory and the practice, in which the students develop multiple personal features and attributes.…”
mentioning
confidence: 99%
See 1 more Smart Citation